Integration in Norway of Children with Special Educational Needs - Sharkey, Maura (REACH: Journal of Inclusive Education in Ireland, 1997)
In May, 1996, twelve representatives from six European countries - Ireland, England, Netherlands, Belgium, Germany & Austria - participated in an ARION study visit to Norway. The purpose of such EU-funded study visits is to allow participants to compare educational systems while also having an opportunity to visit schools and centres in a host country. Maura Sharkey was Ireland's representative on this visit and her report highlights the current special education situation in Norway with a particular focus on integration.